THE DIFFERENCE OF KNOWLEDGE TRANSFER IN LEADERSHIP SUCCESSION IN FAMILY BUSINESS: COMPARATIVE STUDY BETWEEN CHINESE-INDONESIAN AND JAVANESE-INDONESIAN IN MICRO FINANCING INDUSTRY TO HOFSTEDE’S CULTURAL DIMENSIONS - Diego Jason Setianto; Suharnomo Suharnomo (Jurnal Akuntansi dan Pajak, 2023)
This research is a study case research, with the scope of the research is to compare the succession process and knowledge transfer of two family businesses, a Bank Perkreditan Rakyat (BPR) - Credit Bank for the People in Temanggung, Jawa Tengah and a Koperasi Simpan Pinjam - Credit Union in Weleri, Jawa Tengah. A is a credit bank for the people that originates in Temanggung, Jawa Tengah. This is qualitative research that will be using primary data. In this research, an interview will be chosen, due to the ability to dig deep while having the respondent answer freely and without restraint of words and time limit. Due to the nature of the research as a case study, the population researched will be the two specific companies, which are BPR A and Kospin B. Due to the sample characteristics, it is found that the one that fits the purposive sampling characteristics is the old and new Leader of BPR A and the Leader and the son of the Leader of Kospin B. The data analysis technique is qualitative and comparative. Based on the research conducted, the results obtained are: The first factor of successfulness of a succession process is the willingness of predecessor to step down and relinquishing all power. The second factor is the successor’s willingness to step up to the plate, which is very directly shown and stated that since the beginning there is nothing but continuing the family business and legacy and all that the successor have been doing is gearing towards the succession process. The third factor is the actual time spent for the planning stage before the process formally began. The fourth factor is the family’s involvement level is the same before and after the succession process, seeing that the predecessor still hold a big portion of the power and delegates it slowly as the successor became more ready. And, The fifth factor is that everyone accepts the roles given, which could be shown that when the successor was in middle school, they are already happy when the predecessor shared the story without asking for opinion, and only after they were in high school did the predecessor start asking more for their opinion. Keywords: Compare, Knowledge Transfer, Research Case Study, Qualitative, Comparative, Successfulness, Successor’s willingness, Actual Time, Family’s Involvement Level, and Everyone Accepts The Roles Given